The Issue of Grooms Wearing Henna on Their Fingers: An Analysis Based on the Syafii School and Fatwa in Malaysia - Mohd Azhar Abdullah; Irwan Mohd Subri; Muhammad Lukman Ibrahim; Muhammad Amiri Abdul Ghani (Rabbanica: Journal of Revealed Knowledge)
Grooms wearing henna on their fingers in conjunction with weddings is still practised in Malaysian society, especially among Malays and Indians. The difference in the jurisprudence of the four madhabs, especially the Syafii madhab in this issue, also affects the inconsistency of the fatwas of the states in Malaysia. Most of the scientific studies focus more on the benefits of wearing henna according to Islamic, scientific and medical perspectives. However, the study related to the basis of fiqh related to the grooms wearing henna is not detailed. This causes confusion between the prohibition of men wearing henna on their hands due to tashabbuh and women with the need to celebrate the local uruf. This study uses a qualitative methodology through content analysis to examine the views of the Syafii school of jurisprudence in accordance with the uruf in Malaysia as decreed in the states. It aims to harmonize Muslims according to the Malaysian model. The study found that in Malaysia, the Fatwa Committee of the National Council for Islamic Affairs of Malaysia has decided that henna is permitted to be worn by the groom under certain conditions. While at the state level, there is a state fatwa that prohibits henna for the groom, and there is a state fatwa that permits it.